Non-infarct related artery microvascular obstruction is associated with worse persistent diastolic dysfunction in patients with revascularized ST elevation myocardial infarction. (1st February 2020) - Corban, Michel T.; Khorramirouz, Reza; Yang, Shi-Wei; Lewis, Bradley R.; Bois, John; Foley, Thomas; Lerman, Lilach O.; Oh, Jae k; Lerman, Amir
Abstract: Background: Infarct-artery (IRA) microvascular obstruction (MVO) is associated with diastolic dysfunction (DD) in STEMI patients. However, association between nonIRA MVO and DD in STEMI patients remains unknown. We hypothesized that revascularized STEMI patients with IRA and nonIRA MVO (IRA + nonIRA+), compared to those without nonIRA MVO (IRA + nonIRA-), have worse DD at presentation and long-term follow-up. Methods: 87 IRA-revascularized STEMI patients had cardiac magnetic resonance imaging (MRI) [to evaluate MVO] and TTE (to evaluate diastolic function) within 1 week of presentation. Diastolic function was re-assessed by TTE at 3.97 ± 3.24 years. Baseline and follow-up DD prevalence and grade were studied in IRA + nonIRA + vs. IRA + nonIRA- MVO patients. Results: 54 (62%) patients were IRA + nonIRA+ and 33 (38%) IRA + nonIRA-at baseline. IRA + nonIRA + patients had higher DD frequency at baseline (40.7 vs. 6.1%, p = 0.006) and follow-up (50.0 vs. 13.0%, p = 0.05). Only IRA + nonIRA + patients had increase in mitral medial E/e' (20.0%, p = 0.043) and trend towards increase in mitral E/A (31.1%, p = 0.063) at follow-up. IRA + nonIRA + patients had greater left atrial volume index increase (23.7%, p = 0.032 vs. 15.5%, p = 0.029) and smaller prolongation in deceleration time (15.4%, p = 0.018 vs. 18.7%, p = 0.044) at follow-up compared to IRA + nonIRA-. Grade 1 DD increased (60.9–73.9%) and combined grades 2/3 decreased (30.4–13.0%) at follow-up in IRA + nonIRA-patients. In contrast, grade 1 DD decreased (77.8–61.1%) and combined grades 2/3 increased (8.3–22.2%) at follow-up in IRA + nonIRA + patients. Conclusion: Concurrent IRA and nonIRA MVO in revascularized STEMI patients is associated with higher DD prevalence and worse DD grade on long-term follow-up. Highlights: IRA + nonIRA + MVO patients had higher baseline diastolic dysfunction (DD) prevalence. IRA + nonIRA + MVO patients also had higher prevalence of DD at 4-year follow-up. Grade 1 DD decreased and grades 2/3 increased at follow-up in IRA + nonIRA + MVO. Grade 1 DD increased and grades 2/3 decreased at follow-up in IRA + nonIRA- MVO. Abstract : Revascularized STEMI patients with baseline concurrent infarct related coronary artery (IRA) and nonIRA microvascular obstruction (MVO) [IRA + nonIRA+], as compared to IRA + nonIRA- MVO patients, had higher prevalence of diastolic dysfunction at baseline (40.7 vs. 6.1%, p = 0.006) and 4 years follow-up (50.0 vs. 13.0%, p = 0.05). The prevalence of grade 1 diastolic dysfunction increased (60.9–73.9%) and combined grades 2 and 3 decreased (30.4–13.0%) at follow up in patients with IRA + nonIRA- MVO. In contrast, grade 1 diastolic dysfunction decreased (77.8–61.1%) and combined grades 2 and 3 increased (8.3–22.2%) at follow up in patients with IRA + nonIRA + MVO.